(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The paper examines the impact of the devaluation of Iraqi dinar in stimulating the gross domestic product, after the devaluation of Iraqi dinar at the end of 2020. In this context, empirical studies and international experiences have been used. Taking into consideration the rentier economy in Iraq and the dependence of the local market on imported goods in order to meet the aggregate demand. The paper relies on official data and methods of economic analysis. The research problem represented by the weak effectiveness of the previous exchange rate policy in stimulating output and diversifying the Iraqi economy, as well as sacrificing foreign reserves and directing them towards the non-productive commercial sector. The research concluded that stimulating the GDP through devaluation of Iraqi currency requires the availability of supportive and prudent fiscal and trade policies in the medium and long term. The paper recommends addressing the short-term inflationary effects created by a policy of devaluation of the exchange rate